Avaliação do efeito da associação de butirato de sódio e fitase sobre a saúde intestinal e desenvolvimento ósseo de frangos de corte - Layter , Jonas Rodrigo (2019)
The objective of this work was to evaluate the effect of the association of microencapsulated sodium butyrate and phytase on the productive performance, intestinal integrity and bone development of broilers. A total of 736 day-old chicks were used in a completely randomized design in a 2 x 2 factorial scheme (with and without inclusion of sodium butyrate and inclusion of phytase at the recommended dose and super dosing), totaling 4 treatments and 8 replicates of 23 birds each. The inclusion of sodium butyrate in the diets was according to the manufacturer's recommendations (0.750kg / ton) Phytase was included in the concentrations of 750 and 1500 FTU / kg diet. Experimental diets based on corn and soybean meal were formulated to meet the nutritional requirements of broilers from 1 to 14 days and 15 to 28 days. The evaluation of the average weight, feed intake, weight gain and feed conversion was performed weekly. Bone measurements of tibia and femur of weight, length, Seedor index and diameter and densitometry of the tibia were performed at 7 and 28 days. Fragments of the duodenum, jejunum and ileum segments were collected and submitted to morphometry analysis. Statistical analysis of the data was performed using the SAS statistical program. There was no interaction (P <0.05) between the additives at any age evaluated. Poultry receiving supplementation of phytase or sodium-butyrate encapsulated in the diet presented better performance (P <0.05). In the periods from 1 to 14, 1 to 21 and 1 to 28 days, treatments supplemented with sodium butyrate resulted in higher (P <0.05) feed intake and mean weight at 28 days. Sodium butyrate supplementation resulted in greater bone measurements at 7 and 28 days. There was no difference (P> 0.05) between supplementation of the additives on bone densitometry. Supplementation of sodium butyrate increased the crypt width of the ileum at 7 days and at 28 days had no effect on any intestinal segment. The use of phytase in superdosing increased the muscular layer of the duodenum, the length and width of the jejunum villus at 7 days and at 28 days increased the length of the duodenum villi, villi length, villus: crypt ratio, absorption area and muscle layer of the jejunum and decreased the width of the jejunum crypt. The association of sodium butyrate supplementation with phytase superdosing resulted in greater depth and width of jejunum crypt and villous ratio: ileus crypt at 7 days and greater duodenal crypt depth, longer villi length and ileum at 28 days of age.